Technical diagnostics and reliability development of concrete airfield pavements in modernization and reconstruction progress - Malgorzata Linek; Piotr Nita; Adam Poswiata (Przegląd Komunikacyjny)
Abstract: The technical reliability of concrete airport pavements evolves mainly when the project and its technical and functional solutions in all types of industry works is being developed. In the operation process, the technical reliability of the pavement can be shaped as a result of its' modernization and reconstruction. The effect depends primarily on the quality of the works. Currently, the contractors have high-quality materials and specialized equipment minimising human factor in the process of preparing and placing the concrete mix. Potentially high qualifications of technical personnel and other members of the works crew should be a guarantee of high quality works. The operation process must be characterized by a high level of technical culture and rational maintenance procedures. The publication presents the theoretical model of modernized and reconstructed airport's reliability, paying particular attention to the accuracy and efficiency of its technological implementation. Keywords: Pavement reliability; Quality of pavement works; Operational condition; AFE (airport functional elements)